Den falska återkomsten: Om gammal och ny kulturhistoria - Ekström, Anders (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2005)
In the 1980s and 1990s, theoretical developments in the human and social sciences were influenced by a much debated "cultural turn". One outcome of this in historical research was a renewed interest in the concept of "cultural history". In an anthology published in 1989 by the American historian Lynn Hunt, "the new cultural history" was launched as a critique of some of the basic conceptions of social history and the Annales school. The main purpose of this article is to review the theoretical debates that motivated the new cultural history, and to discuss some of its key concepts, most notably the concepts of culture and representation. However, since recent discussions in Scandinavia and elsewhere has been as much concerned with the general historiography of cultural history, I also explore the ways in which the "new" cultural history can be related to the "old" cultural history of the 18th and 19th centuries. In conclusion, I argue that the turn towards cultural analysis in historical research has been the productive outcome of a particular kind of transdisciplinarity rather than developments within the established disciplines.